ANALISIS FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENDAPATAN BERSIH NELAYAN RAWAI DI KECAMATAN TELUK AMBON - Willem Talakua (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
One  of  the subdistricts  in the  city  of Ambon,  most  people work  as  fishermen are Ambon  Bay subdistrict. In these subdistrict there is a unit of long line effort that afforded by the local fishermen to the  characteristics  of small-scale  businesses.  The  resulting production is  sold and consumed by households fishing (subsistence  farmer).  This  research aims  to analyze  the net income  of fishermen and socioeconomic factors that affect net income of long line fishing. The data was collected through surveys and interviews,  as well  as from secondary data.  Analysis  of the  data used is  the  analysis  of income and multiple linear regressions. The results showed that the net income earned during the one year fishermen are Rp 45.556.046, and net income each month is Rp 3.796.337. While socioeconomic factors  that  affect  long  line  fishermen  net  income  are:  investment  costs  (X1),  operating  costs  (X2), fishing trip (X3), production (X4), and business experience (X5). Key words: Socioeconomic factors, net income, long line fishermen.